PENINGKATAN FOKUS PERHATIAN DALAM PEMBELAJARAN TARI MELALUI KEGIATAN ROLE PLAYING BERBASIS KINESTETIK (PTK SISWA EKSTRAKURIKULER SMPN 76 JAKARTA PUSAT) - Ivana, Esa Aura; Elindra Yetti; Selly Oktarini (Jurnal Pendidikan Tari, 2025)
This study aims to improve students' focus of attention in dance learning through the application of kinesthetic-based role playing methods. Focus of attention is an important component in achieving learning objectives, especially in dance learning that requires concentration and coordination of movement. Kinesthetic-based role playing was chosen because it combines elements of movement exploration and active student roles which are believed to be able to stimulate optimal mental and physical involvement. This study uses a classroom action research (CAR) methodology with the John Elliot model, using quantitative statistical analysis and descriptive qualitative analysis. Data collection techniques through observation, pretest, interviews and documentation on collaborators and dance extracurricular students of SMPN 76 Central Jakarta. This study was conducted in 3 cycles on 35 students. Improvements can be seen from students' active participation, concentration when following instructions, and creativity when exploring dance movements. Based on the results of the N-Gain analysis in this study, a value of 0.7 was shown in the high category. Through Kinesthetic-Based Role Playing Activities, students' focus of attention in dance learning in the dance extracurricular of SMPN 76 Central Jakarta is improved.